Verb Complements in the Eastern Armenian Treebanks UD_Armenian-ArmTDP and UD_Armenian-BSUT - Danielyan, Anna; Yavrumyan, Marat (Bulletin of Yerevan University B: Philology, 2024)
The comparability of morphological and syntactic annotations of multilingual corpora is a crucial aspect of Natural Language Processing (NLP). The Universal Dependencies (UD) platform, which aims to identify the universal features of languages by identifying dependencies, serves this purpose and has become one of the largest and continuously growing collections of such corpora, especially in the last decade. The UD framework has become a platform for building the UD_Armenian-ArmTDP and UD_Armenian-BSUT treebanks for modern Eastern Armenian. This article presents the types of syntactic relations selected for parsing verb complements in these treebanks from the cross-linguistically applicable set of relations in UD, together with their equivalents in Armenian grammar. Furthermore, we present some challenges associated with parsing Armenian verb complements and possible solutions within the UD taxonomy.